Analisis Pertimbangan Hakim Mengenai Unsur Melawan Hukum dalam Pasal 2 Ayat (1) Undang-Undang Nomor 31 Tahun 1999 jo. Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi - Pratama, Angga; Danil, Elwi; Fendri, Azmi (UNES Law Review, 2023)
This research will examine the analysis of the judge's considerations regarding the element of unlawfulness in Article 2 Paragraph 1 of Law Number 31 of 1999 in conjunction with Law Number 20 concerning the Eradication of Corruption Crimes. Study of the Padang District Court Corruption Court. The research method used is normative research or literature study assisted by interviews as supporting data. This research is a descriptive analysis because this research is expected to provide a concrete picture regarding the interpretation of the unlawful element in Article 2 paragraph 1 of Law Number 31 of 1999 in conjunction with Law Number 20 concerning the Eradication of Corruption Crimes. The results of the research are that the element of unlawfulness in material terms no longer has binding legal force, while formally the element of unlawfulness in criminal acts of corruption still has binding legal force, which means that a person can be punished if the act is committed. violate statutory regulations.